STATUS BERAT BADAN MENCIT (Mus musculus) BALB/C SETELAH INFEKSI Plasmodium berghei - Syukriah Syukriah (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2019)
Malaria is an infectious disease caused by Plasmodium, which is a single-celled creature that belongs to the group of protozoa. This disease attacks all age groups, both men and women. Malaria can cause death especially in high risk groups namely infants, children under five, pregnant women, besides malaria directly causes anemia and can reduce work productivity. The study design uses a complete randomized design  with 4 treatment groups. Group 1 is the control group without any treatment. Group 2 was injected with 1 × 102 iRBC. Group 3 is injected with 1 × 103 iRBC. Group 4 was injected with 1 × 104. The treatment was given for 30 days. Measurement of body weight was done every day. Examination of the degree of parasitemia was carried out on day 3 after infection with the thin blood smear method. Data measured body weight and degree of parasitemia were analyzed by one way ANOVA and DMRT tests at a significant level of 5%. The results showed a significant difference in body weight between mice infected with parasites versus those not infected. The more doses of parasites that were infected the more it will affect the mice. The conclusion of this research is P. berghei infection gives weight loss effect on balb/c mice. Keywords: malaria, Plasmodium berghei, weight